Pentingnya Sekolah Bertaraf Internasional di Bali - I Ketut Sudarsana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
This study aims to analyze the International School Pilot Program in Bali, where there is a phenomenon in the community who questioned the quality of the school that raised its status to international school stubs, and many consider that the program is only to enrich the school and to give the impression that the school with the program this is better than other schools. Therefore, in order to avoid misperceptions between the implementation process and the material contained in the guidebook of the implementation of international school stubs, it is necessary to have a clear picture of the overall program.